Impact of criminal act of terrorism on economy. (February 2019) - Pratiwi, E T; Abdullah, L O D; Abdullah, R; Wardana,; Muhammad, R
Abstract: The crime of terrorism is one of great evil. The research aims to identify the impact of criminal acts of terrorism on the economy which resulted in economic losses in the last two decades. The economic effect of terrorism on economic is on the rise. The central government becomes the one who suffered most of the economic impact due to terrorism. In ASEAN, Indonesia ranked 42 with a score of 4.55. Countries with a higher level of vulnerability than Indonesia is the Philippines which ranked 11th with a score of 7.12. Thailand ranked 16th with a score of 6.6 and Myanmar ranked 37 with a score of 4.95. understanding the significant economic impact, the Government needs mitigation efforts comprehensively in order to prevent terrorism. Protecting strategic places, especially the business and economy center becomes essential in order to minimize the economic impact. Moreover, the government needs to take some comprehensive action to prevent acts of terrorism.